Altitude training: who benefits? - Smith, M. H.; Sharkey, B. J. (The Physician and Sportsmedicine, 1984)
Critical meaning of the author on the hand of many years of experiences and a lot of studies on the sense of altitude training. Conclusion: A critical reading of the literature casts doubt on the value of altitude training, at least for some athletes.